2019
DOI: 10.1186/s12931-019-1234-4
|View full text |Cite
|
Sign up to set email alerts
|

The biomarkers suPAR and blood eosinophils are associated with hospital readmissions and mortality in asthma – a retrospective cohort study

Abstract: IntroductionPrognostic biomarkers in asthma are needed. The biomarker soluble urokinase plasminogen activator receptor (suPAR) has been associated with asthma control and with prognosis in acutely admitted medical patients. We investigated if suPAR and blood eosinophil counts at the time of admission for asthma are associated with readmission and mortality.MethodsOur cohort comprised 1341 patients (median age 45.3, IQR 30.1–63.1) acutely admitted with a diagnosis of asthma to Hvidovre Hospital, Denmark (Novemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 42 publications
(43 reference statements)
0
21
0
2
Order By: Relevance
“…Eosinophils (EOSs) are key innate immune cells in host defence, [3] and they have been found to be associated with mortality in patients with chronic obstructive pulmonary disease (COPD) [4,5] and asthma. [6,7] The blood EOS counts are considered as a potential biomarker for identifying COPD patients at risk and as a reference for the usage of inhaled corticosteroids. [8] For ARDS, EOSs have been considered as an important immune response contributor, and they may be a diagnostic biomarker.…”
Section: Introductionmentioning
confidence: 99%
“…Eosinophils (EOSs) are key innate immune cells in host defence, [3] and they have been found to be associated with mortality in patients with chronic obstructive pulmonary disease (COPD) [4,5] and asthma. [6,7] The blood EOS counts are considered as a potential biomarker for identifying COPD patients at risk and as a reference for the usage of inhaled corticosteroids. [8] For ARDS, EOSs have been considered as an important immune response contributor, and they may be a diagnostic biomarker.…”
Section: Introductionmentioning
confidence: 99%
“…However, the relationship between blood eosinophils and outcome has not been consistently clari ed in patients with asthma and those with COPD. In asthma, Price et al [7] reported that higher blood eosinophil counts are associated with more severe exacerbations and poorer asthma control, while Håkansson et al [6] found that a lower blood eosinophil count was related to both one-year readmission and mortality. In COPD, Casanova's longitudinal study [17] showed that patients with higher blood eosinophil counts for 2 years were more inclined to have a longer survival time.…”
Section: Discussionmentioning
confidence: 99%
“…Eosinophils are key innate immune cells in host defence [3], and they have been found to be associated with mortality in patients with chronic obstructive pulmonary disease (COPD) [4,5] and asthma [6,7]. The blood eosinophil count (EOS) is considered a potential biomarker for the identi cation of COPD patients at risk and as a reference for the usage of inhaled corticosteroids, as recommended by the GOLD 2019 guidelines [8].…”
Section: Introductionmentioning
confidence: 99%
“…Провоспалительные медиаторы, секретируемые эозинофилами, вызывают повреждение эпителия, инициируя расширение сосудов, сокращение гладких мышц и повышенную секрецию слизи, что, в свою очередь, связано с повышенной гиперреактивностью дыхательных путей, симптомами БА и сужением дыхательных путей. Инициируя позднюю фазу воспаления, эозинофилы обеспечивают ремоделирование дыхательных путей [10,11]. Эозинофилы модулируют воспалительный процесс, продуцируя большое количество факторов, таких как токсические основные (щелочные) белки, липидные медиаторы, цитокины и супероксид-анионы.…”
Section: современные данные о патогенезе баunclassified
“…Отмечено, что эозинофильная инфильтрация дыхательных путей сохраняется у детей с тяжелой формой БА, несмотря на использование высоких доз ингаляционных глюкокортикостероидов [12]. В то же время молекулярные механизмы, быстро и специфически регулирующие уровень эозинофилов, остаются малоизученными [10]. В активации эозинофилов ключевым фактором является интерлейкин-5 (ИЛ-5), поскольку рецепторы для этого цитокина экспрессируются преимущественно на эозинофилах [13].…”
Section: современные данные о патогенезе баunclassified